Differential modulation of SARS-CoV-2 infection by complement factor H and properdin - Kishore, Uday; Varghese, Praveen M.; Kumar, Chandan; Idicula-Thomas, Susan; Mayora Neto, Martin; Tsolaki, Anthony G.; Ponnachan, Pretty; Masmoudi, Khaled; Al-Ramadi, Basel; Vatish, Manu; Madan, Taruna; Temperton, Nigel; et al. (Frontiers in Immunology, 2025)
IntroductionAn unbalanced immune response and excessive inflammation are the major hallmarks of severe SARS-CoV-2 infection, which can result in multiorgan failure and death. The dysregulation of the complement system has been shown in various studies as a crucial factor in the immunopathology of SARS-CoV-2 infection. Complement alternative pathway has been linked to the excessive inflammation in severe SARS-CoV-2 infection in which decreased levels of factor H (FH) and elevated levels of properdin (FP) were observed. The current study investigated the potential immune protective roles of FP and FH against SARS-CoV-2 infection.MethodsThe interactions between FH and FP and the SARS-CoV-2 spike (S) and its receptor binding domain (RBD) were evaluated using direct ELISA. The cell binding and luciferase-based viral entry assays utilising S protein expressing lentiviral pseudotypes were used to evaluate the possible modulatory effects of FH, FP, and recombinant thrombospondin repeats 4 and 5 (TSR4 + 5) on SARS-CoV-2 cell entry. Using RT-qPCR, we also assessed the immunomodulatory roles of FH and FP in the cytokine response induced by SARS-CoV-2 pseudotypes.ResultsFH and FP were found to bind to both the RBD and SARS-CoV-2 S proteins. The treatment of FP or TSR4 + 5 enhanced cell binding and entry of SARS-CoV-2 pseudotypes that was administered in A549 cells expressing human ACE2 and TMPRSS2 (A549-hACE2+TMPRSS2 cells). FP increases the affinity between host ACE2 and SARS-CoV-2, according to in silico work. In A549-hACE2+TMPRSS2 cells, the effect of FP on viral cell entry and binding was counteracted by anti-FP antibody treatment. On the other hand, SARS-CoV-2 lentiviral pseudotypes’ cell entry and binding were decreased by FH treatment. The A549-hACE2+TMPRSS2 cells that were challenged with SARS-CoV-2 alphaviral pseudotypes (expressing spike, envelope, nucleocapsid, and membrane proteins) pre-treated with FP or TSR4+5 showed an upregulation of pro-inflammatory cytokine transcripts, including NF-κB and IL-1β, IL-8, IL-6, TNF-α, IFN-α, and RANTES. Contrary to this, the expression of these pro-inflammatory cytokines was downregulated by FH treatment. FH treatment decreased S protein-mediated NF-κB activation, but FP treatment enhanced it in A549-hACE2+TMPRSS2 cells. DiscussionThese results imply that FH may function as a SARS-CoV-2 cell entry and binding inhibitor, reducing the inflammatory response linked to infection independently of complement activation. FP could aid cell viral entry and binding and aggravate hyperinflammation that might contribute to the severity of the infection.